2020
DOI: 10.2147/dddt.s264122
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel Molecular Mechanism of Aspirin and Celecoxib Targeting Mammalian Neuraminidase-1 Impedes Epidermal Growth Factor Receptor Signaling Axis and Induces Apoptosis in Pancreatic Cancer Cells</p>

Abstract: Background: Aspirin (acetylsalicylic acid) and celecoxib have been used as potential anticancer therapies. Aspirin exerts its therapeutic effect in both cyclooxygenase (COX)-dependent and-independent pathways to reduce tumor growth and disable tumorigenesis. Celecoxib, a selective cyclooxygenase-2 (COX-2) inhibitor, reduces factors that cause inflammation and pain. The question is whether aspirin and celecoxib have other molecular targets of equal or more therapeutic efficacy with significant anti-cancer preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 62 publications
(123 reference statements)
0
27
0
Order By: Relevance
“…This may be due to the reduced clonogenic potential of cells following treatment, suggesting that ASA+OP+GEM treatment preferentially targets malignant cells with stem cell-like properties, such as regenerative capacity (Figures 4 and 5). Given that we have reported on the role of OP [23,28] and ASA [22] in targeting and shutting down Neu-1 activity in complex with growth factor receptors, these findings are not surprising. A recent study reported on Neu-1 suppressing bladder cancer progression by inhibiting the fibronectin-integrin α5β1 interaction and the Akt signaling pathway [47].…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…This may be due to the reduced clonogenic potential of cells following treatment, suggesting that ASA+OP+GEM treatment preferentially targets malignant cells with stem cell-like properties, such as regenerative capacity (Figures 4 and 5). Given that we have reported on the role of OP [23,28] and ASA [22] in targeting and shutting down Neu-1 activity in complex with growth factor receptors, these findings are not surprising. A recent study reported on Neu-1 suppressing bladder cancer progression by inhibiting the fibronectin-integrin α5β1 interaction and the Akt signaling pathway [47].…”
Section: Discussionmentioning
confidence: 55%
“…We believe that the combination of ASA+OP can interfere with EMT that is triggered by chemotherapy, and this is likely the reason for its effectiveness. In support of this premise, we have previously reported that GEM-resistant PANC-1 (PANC-1-GemR) cells treated with increasing concentrations of ASA (0.1 to 10 mM) revealed a significant concentration-and time-dependent decrease in cell viability [22]. It is noteworthy that resistance to GEM can involve multiple mechanisms, such as altered apoptotic regulating genes and altered expressions or sensitivities of enzyme targets.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations